The symbolic structures of social life: integrative comments on the social thinking architecture / As estruturas simbólicas da vida social: comentários integrativos sobre a arquitetura do pensamento social - Wachelke, João (Psicologia e Saber Social, 2014)
ABSTRACT: The present paper is an essay that aims at contributing to the debate on the social thinking architecture, a theoretical hierarchical model originally proposed by Rouquette that establishes relations between various symbolic formations. Other than addressing the main characteristics of social thinking and the architecture, a broad review of the role of its classical constructs is presented, i.e. social representations, ideologies, attitudes, thêmata and opinions. A discussion about other constructs such as nexus, social images and collective representations and their position in the architecture is also provided. Keywords: social thinking; social thinking architecture; structural approach; social representations; symbolic formations. RESUMO: O presente artigo é um ensaio que visa a contribuir para o debate sobre a arquitetura do pensamento social, um modelo teórico hierárquico proposto originalmente por Rouquette que estabelece relações entre diversas formações simbólicas. Além de tratar das principais características do pensamento social e da arquitetura, uma revisão ampla do papel de seus construtos clássicos é apresentada, isto é, representações sociais, ideologias, atitudes, thêmata e opiniões. Uma discussão sobre outros construtos como nexus, imagens sociais e representações coletivas e suas posições na arquitetura também é fornecida. Palavras-chave: pensamento social; arquitetura do pensamento social; abordagem estrutural; representações sociais; formações simbólicas.